Derivation of Point Plot-based Ductile Fracture Loci through Assimilation of Finite Element Simulation and Individual Actual Punched Surface Profile - Matsuno Takashi; Eguchi Jin; Kunii Yasuhiro; Shimizu Kazuyuki; Matsuki Yuichi; Shinmiya Toyohisa; Iizuka Eiji (MATEC Web of Conferences)
This study demonstrated the inverse identification of the ductile fracture locus (DFL), successfully reproducing the actual punched surface profiles of DP980 steels. The primary aim was to visualize the plastic strain and residual stress distribution in the observed punching surface cross-section. First, cracks were incorporated into finite element (FE) half-punching simulations, on the basis of preliminary observations of the actual crack propagation behavior, to replicate individual punched surface profiles. Notably, ductile fracture modeling was not employed during the initial FE simulation. Then, the equivalent plastic strain and historical-averaged stress triaxiality were plotted for two distinct element groups: those immediately before crack propagation (fracture region) and those unaffected by the crack (non-fracture region). The DFL was inversely identified as the boundary between the fracture and non-fracture regions. Subsequently, the identified DFL was integrated with Xue's damage integration scheme for FE punching simulations. This approach successfully reproduced the punched surface profiles. The DFL exhibited robustness under various punching conditions. FE simulations with different punching clearances yielded punched surface profiles that agreed well with the experimental observations, although slight variations were noted in the fracture surface portion.